2014
DOI: 10.1111/apm.12275
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antinuclear antibodies by indirect immunofluorescence and line immunoassay methods′: four years′ data from Turkey

Abstract: The presence of antinuclear antibodies (ANAs), directed against intracellular antigens, is a hallmark of systemic autoimmune rheumatic diseases. The indirect immunofluorescence (IIF) assay is among the most commonly used routine methods for ANA detection as the screening test. The objective of the study was to evaluate ANA patterns in a 4-year period retrospectively. All 19 996 serum samples that were sent to the Laboratory of Medical Microbiology of the tertiary Hospital by any hospital department between 1 J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
5
7
1
Order By: Relevance
“…Our study presents an ANA prevalence of 14.3% in non‐SARD patients, similar to that in general population reported previously , suggesting that various other diseases rather than SARDs cannot increase the risk of ANA production. Admittedly, since non‐SARDs were not specified in the current study, the conclusion must be explained in caution.…”
Section: Discussionsupporting
confidence: 90%
“…Our study presents an ANA prevalence of 14.3% in non‐SARD patients, similar to that in general population reported previously , suggesting that various other diseases rather than SARDs cannot increase the risk of ANA production. Admittedly, since non‐SARDs were not specified in the current study, the conclusion must be explained in caution.…”
Section: Discussionsupporting
confidence: 90%
“…Only two other studies have been undertaken in India, in Bangalore by Sebastian et al 8 and in Chandigarh by Minz et al 6 Although the frequency of positivity in Bangalore was similar to the present study, Chandigarh showed a lesser positivity ( Table 6 ). Similar hospital-based studies done in Turkey by Zafer et al 9 and Sener et al 10 and in Belgium by Peene et al 7 had lesser positivity rate compared with present study. Although the results of these studies cannot be considered as prevalence, yet an estimation of disease burden can be made.…”
Section: Discussionsupporting
confidence: 89%
“…However, the present study and studies done by Chanwit et al and Sener et al found the rare ANA patterns in significant number, and also disease conditions associated with them, especially chronic hepatic conditions and carcinoma. 10 11 This supported the extensive study done by Pieter et al on rare ANA patterns, and his conclusion of nuclear envelope and nuclear dot patterns was associated with autoimmune hepatitis and hepatic and colon carcinoma. 17 The cytoplasmic patterns are also considered nondisease-specific but their significance should not be ignored, as stated by Chanwit et al, since they might as well point to certain undetected conditions.…”
Section: Discussionsupporting
confidence: 83%
“…We found a higher rate of positive specific antibodies than previous study (35% vs. 16.9%). 14 Compared to previous studies that performed antigenspecific assay in all IIF-ANA negative sera and who found a rate of positivity of 0.7-14% [15][16][17] , we demonstrated that screening with EIA-ANA before performing antigenspecific assay in IIF-ANA negative sera may increase the probability of identifying specific antibodies.…”
Section: Discussionmentioning
confidence: 51%